The Doctor’s Anatomy: The Androgynous Performance of Gender and (Neo-)Victorian Sexual Politics in Patricia Duncker’s James Miranda Barry - Ureczky, Eszter (Hungarian Journal of English and American Studies, 2021)
Patricia Duncker’s 1999 neo-Victorian novel is a fictional biography of the legendary Victorian military surgeon, James Miranda Barry, rumored to be a hermaphrodite. Duncker’s postmodern feminist fiction recreates the medical discourse, as well as the body and sexual politics of the Victorian era by writing these nineteenth-century somatic ideologies onto the ambiguously gendered body of Barry. Interrogating the poetic and political strategies of creating medicine as a masculinized profession from a cultural studies point of view, the essay argues that Duncker’s novel can be contextualized within a recent tendency in contemporary British fiction that could be hypothesized as medico-historical metafiction, indirectly addressing twenty-first-century biopolitical questions about the cultural inscription of gender roles and bodily normality by (re)telling a Victorian narrative. These questions are examined from three aspects: the neo-Victorian historical novel as a feminist genre, the androgyne as a late-Victorian subtype of the grotesque freak, and nineteenth-century female identities as the reservoir of disempowering pseudo-choices. (EU)